Secreted metabolite-mediated interactions between rhizosphere bacteria and Trichoderma biocontrol agents. - Ningxiao Li; Md Tariqul Islam; Seogchan Kang (PLoS ONE)
Trichoderma has been used as an alternative to synthetic pesticides to control a variety of phytopathogenic fungi, oomycetes, and nematodes. Although its mechanism of pathogen suppression has been extensively studied, how Trichoderma interacts with non-target microbes is not well understood. Here, we investigated how two Trichoderma biological control agents (BCAs) interact with rhizosphere bacteria isolated from a tomato plant via secreted proteins, metabolites, and volatile compounds (VCs). Culture filtrates (CFs) of T. virens and T. harzianum, containing secreted proteins and metabolites, strongly inhibited (>75% reduction in growth) 39 and 19, respectively, out of 47 bacterial strains tested. Their CFs inhibited the remaining strains at lower degrees. Both metabolites and proteins are involved in inhibiting bacteria, but they seem to antagonize each other in inhibiting some strains. Trichoderma and bacteria suppressed the growth of each other using VCs. The secretion of antibacterial and antifungal molecules by T. virens and T. harzianum was significantly affected by VCs from some bacteria, suggesting that both Trichoderma BCAs and rhizosphere bacteria use VCs to influence each other in multiple ways. In light of these results, we discuss how metabolite-mediated interactions can potentially affect the effectiveness of biocontrol.